Analisis Sistem Informasi Akuntansi Penerimaan Uang Pendaftaran Calon Murid Baru: (Studi Kasus SMK Bintang Harapan) - Rizkison Rizkison; Donna Agustin (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to assess the adequacy of accounting information system of new student registration fee in Vocational High School (SMK) Bintang Harapan Cibarusah. With an adequate accounting information system, it is expected that the school can produce reliable, relevant and complete information. The information will be used for decision making by the school and external parties. Therefore, sufficient accounting information system is needed to achieve all accounting information system objectives. This type of research was a case study. The data used in this research was obtained by observation, interview, and documentation. Data analysis techniques used by researchers were comparison and classification between the realization of SMK Bintang Harapan with the theory. The results of this study indicate that there were four components of accounting information system cash receipts in school: data collection, data processing, reporting, and control. that had not been fully adequate because it had not been able to support the achievement of accounting information system objectives. Components of people were sufficient. Components of procedures and instructions were unable to meet the achievement of accounting information system objectives because it had not produced reliable, relevant, and complete accounting information. The components of data was not sufficient because the data written on a ledger was data from a cash book so that the existing data become less accurate and relevant. The internal control components had not been able to provide financial and other information on time according to the tasks.